Translation Shift And Accuracy in The Translation Of Students’ Writing in Recount Text at Third Semester of English Department Nommensen HKBP University - Rosalina Kacaribu (Jurnal Scientia, 2022)
Translation is used to learn and comprehend a foreign language. The effect of the phenomenon may be observed in a variety of translated films, books, novels, newspapers, articles, writings, and so on. When translating, if indeed the researcher cannot find an equivalent pattern in both the source and target languages, the translator needs to shift the translation into the target language; As a result, both languages have a common understanding. In conducting this research, the researcher choose students at Third Semester of English Department Nommensen HKBP University writing recount text as the data, in students writing the researcher will analyze the translation shift and check the accuracy of the writing. This study uses qualitatative methods with documentary technique to get the results of students’ writing in recount text and interview. This research the researcher using Catford Theory to classify translation shifts and using Nababan Assessment of Accuracy Aspect. The purpose of this research is to finding kinds of translation shifts that occur in the research also to finding the accuracy that includes accurate, less accurate, and inaccurate in students writing The result of this study is there are four shifts (structure shift, unit shift, class shift, intra-system shift) occur in the translation of students’ writing in recount text at third semester of English Department Nommensen HKBP University, the most used shift is structure shift. The accuracy score are, accurate translation: 44,4%, less accurate translation: 50,7%, and inaccurate translation: 4,9%. The translation of students’ writing in recount text at third semester of English Department Nommensen HKBP University is less accurate.